Thermodynamic challenges for CO2 pipelines design: A critical review on the effects of impurities, water content, and low temperature. (February 2022) - Vitali, Matteo; Corvaro, Francesco; Marchetti, Barbara; Terenzi, Alessandro
Highlights: The main thermodynamic challenges associated with CO2 transport via pipeline has been analysed. A critical review of main flow-assurance issues related to CO2 pipelines has been presented. The impact of impurities, typology and their concentrations has been included. Corrosion control strategies and water content limits have been collected through a literature review. A collection of design parameters useful to technicians and operators has been reported. Abstract: Environmental issues related to climate change have constantly been increasing in the last years, and global emissions must be managed wisely, adopting the most powerful and effective strategies available. Carbon Capture Utilization and Storage (CCUS) is claimed as a solid climate mitigation strategy for the most challenging emissions and the production of blue hydrogen. The development of an international CO2 transportation network is considered a necessary cross-cutting topic in the whole Carbon Capture and Storage sector. CO2 pipeline development is an essential aspect for the realization of most decarbonization CCS projects. Large-scale CCS projects will require the management and transport of CO2 in the presence of impurities at lower costs than traditional CO2 pipelines utilized for Enhanced Oil Recovery (EOR). Thus, the accuracy of modelling carbon dioxide in the presence of other components needs to be assessed. Corrosion prediction and control are strongly related to water content and introduces uncertainties in terms of costs and corrosion risks, especially in the presence of other components and possible cross-chemical reactions. In this work, the process and flow assurance challenges related to the design of a CO2 pipeline have been reviewed in terms of impurities, water content, and corrosion, as well as low-temperature scenarios. The main scope of this paper is to analyse the aspects that can be improved and the ones that need for further research from a thermodynamic point of view. This will help the design of a next generation of CO2 pipelines with low CAPEX (capital expenditure) and OPEX (operating expense), suitable for large-scale CCS projects and meeting the Paris Agreements.